Imperfect Captions Paired to Audiovisual Stimuli Improve Speech Recognition but Do Not Reduce Listening-Related Fatigue. - Esser, Katie; Picou, Erin M.; Hornsby, Benjamin W. Y. (American Journal of Audiology, 2025)
Purpose: Understanding speech in challenging environments can be fatiguing for individuals with and without hearing loss. Empirical research examining interventions to reduce such fatigue, however, is limited. Our study investigated the effects of imperfect captions, such as those created using automated speech recognition systems, on listening-related fatigue during a challenging speech task. Method: Twenty-two adults (aged 18--63 years) with essentially normal hearing completed a sustained dual task designed to induce listening-related fatigue. The primary task was audiovisual sentence recognition in quiet, with speech levels individually adjusted for ~70% correct performance (without captions). The secondary task was response time (RT) to topic words presented during the speech task. Participants completed the dual task with or without captions. Subjective fatigue ratings were obtained before, during, and after the dual task. Vigilant attention was measured via the secondary task and before and after the dual task using visual stimuli (RTs to a visual marker presented at random intervals). Results: Subjective fatigue ratings increased significantly over the course of the dual task. However, this increase was larger for the group who had captions, even though they had better sentence recognition overall. Evidence of behavioral fatigue (slowed RTs over time) was also present but only for those in the Caption group. Anecdotal reports from study participants suggest that the increased fatigue for the Caption group was related to the cognitive challenge of combining information from the time-locked audiovisual cues and the time-delayed, and imperfect, text captions. Conclusions: Even though they were time-delayed and contained inaccuracies, captions improved speech recognition. However, this benefit was accompanied by greater increases in subjective and behavioral fatigue. Therefore, in some conditions imperfect captions can have negative consequences for listening-related fatigue. Further research is needed to determine whether this pattern holds in different circumstances, such as with audio-only stimuli. Supplemental Material: https://doi.org/10.23641/asha.29646482